The neuroelectrophysiological and behavioral effects of transcranial direct current stimulation on executive vigilance under a continuous monotonous condition - Dai, Jing; Wang, Hang; Yang, Lin; Wang, Chunchen; Cheng, Shan; Zhang, Taihui; Ma, Jin; Wen, Zhihong; Cao, Xinsheng; Hu, Wendong (Frontiers in Neuroscience, 2022)
A prolonged period of vigilance task will lead to vigilance decrement and drop in cognitive efficiency. Although transcranial direct current stimulation (tDCS) can be used to improve cognitive performance following vigilance decrement, findings are inconsistent. This study aims to study the neuroelectrophysiological and behavioral effects of tDCS over the left dorsolateral prefrontal cortex (DLPFC) on executive vigilance under a continuous monotonous condition. We recruited twenty nine participants who randomly received 30 min active or sham tDCS before the vigilance task [anode electrode at the left DLPFC, cathode electrode at the right supraorbital area]. Participants completed four sessions of vigilance task and five sessions of self-report sleepiness, Oddball task, Go/Nogo task, for a total of about five hours. EEG was acquired in real time throughout the experiment. Repeated measures ANOVA was utilized to analyze the evolution of each metric with task-on-time. The results demonstrated that subjective arousal state, vigilance performance, event-related potentials (ERPs) and EEG power were significantly affected by time on task. Brain stimulation did not significantly affect the evolution of subjective and objective executive vigilance performance, but significantly modulated spontaneous activity in the alpha and beta bands across the entire brain. The continuous enhancement of the prefrontal cortex increased P2 amplitude for Oddball task, which was associated with the enhancement of the early stage of information processing. P3 amplitude had a temporary enhancement effect, while significantly decreased following cognitive fatigue. TDCS had a continuous enhancement effect on N2 amplitude for Go/Nogo task, which was associated with the enhanced inhibition of distracting stimuli. Together, the current data suggest that anodal tDCS over left DLPFC possibly both enhance the early stage of relevant information processing and the inhibitory control of distracting stimuli during a continuous and monotonous vigilance task.